Acrosomal integrity of buffalo spermatozoa and its relationship to fertility - PANT, H C; BAROT, L B; KASIRAJ, R; MISRA, A K; PRABHAKAR, J H (The Indian Journal of Animal Reproduction, 2023)
Acrosomal integrity of neat semen often Murrah buffalo bulls was evaluated by giemsa staining. Eightbulls had >90 per cent spennatozoa with intact acrosomes, while in two bulls the; intact acrosomes averaged 67.9and 79.8 per cent. In these two bulls many ejaculates showed a high incidence of detached acrosome; mean valuesbeing 16.9 and 18.8 percent as against2.4 to 7.4 per cent in the remaining bulls. Two consecutive weekly ejaculatesfrom a bull with a very low and high incidence of detached acrosome were frozen and used in field Al trial. Theconception rate declined by 11.2 per cent when incidence of detached acrosome increased from 3.4 to 26.0 per cent.These results indicated that among various measurements of ejaculate quality, acrosomal evaluation would helpto identify bulls with potentially lowered fertility.
Keywords: Acrosomal integrity; fertility; buffalo; spermatozoa; semen evaluation